QUALITY CONTROL OF MICROBIOLOGY LABORATORY - Tri Umiana Soleha (JUKE Unila, 2014)
In recent years the establishment of quality standards for goods and services is considered by society at large. One of these is laboratory quality standards. Results of laboratory tests of quality in terms of accuracy, precision, speed, usability, and low cost. In the clinical laboratory, quality control system is one of the steps that must be done in the process of analyzing a sample. [JuKe Unila 2014; 4(8):276-284]